Dual-stimulus magnetoelectric energy harvesting. (9th March 2018) - Chu, Zhaoqiang; Annapureddy, Venkateswarlu; PourhosseiniAsl, MohammadJavad; Palneedi, Haribabu; Ryu, Jungho; Dong, Shuxiang
Abstract: Abstract : Harvesting energy from otherwise wasted resources has been intensively investigated as a promising technology especially for enabling the deployment of autonomous wireless-sensor networks for the Internet of Things. Multi-stimulus energy harvesting, simultaneously from different energy sources, provides an attractive opportunity to amplify the power density of harvesters, thereby extending their potential for self-powered devices. In this article, we review recent and ongoing research efforts aimed at enhancing the energy-harvesting performance of magnetoelectric (ME) composite harvesters employing dual stimuli, mechanical vibrations, and magnetic fields. After a brief introduction to vibration, magnetic field, and dual-mode energy harvesting, we survey the key materials utilized for ME energy harvesting. We then focus on progress in this area and discuss relevant ideas to realize electromechanical and magnetoelectric coupling for harvesting energy from mechanical vibrations and magnetic fields simultaneously. We provide perspectives and future directions as well.